2 END-TO-SIDE NEURORRHAPHIES AND NERVE GRAFT WITH REMOVAL OF THE EPINEURAL SHEATH - EXPERIMENTAL-STUDY IN RATS - Viterbo, Fausto [UNESP]; Trindade, J. C.; Hoshino, K.; Mazzoni, A. (Churchill Livingstone, 1994)
We have studied a new type of end-to-side nerve repair in rats. The healthy (donor) nerve was not divided but an epineural window was created. In our experiment, a nerve graft bridged the tibial nerve to the distal end of the divided peroneal nerve. Electrophysiological studies showed electrical impulses conducted through both end-to-side nerve junctions. Histological studies demonstrated axons leaving the lateral surface of the healthy (donor) nerve. Based on these observations, we suggest that end-to-side neurorrhaphy from a healthy nerve may bridge a neural deficit.